Psychometric evaluation of instruments measuring the work environment of healthcare professionals in hospitals: a systematic literature review - Maassen, Susanne M (Int J Qual Health Care, 2020)
PURPOSE: Research shows that the professional healthcare working environment influences the quality of care, safety climate, productivity, and motivation, happiness, and health of staff. The purpose of this systematic literature review was to assess instruments that provide valid, reliable and succinct measures of health care professionals’ work environment (WE) in hospitals. DATA SOURCES: Embase, Medline Ovid, Web of Science, Cochrane CENTRAL, CINAHL EBSCOhost and Google Scholar were systematically searched from inception through December 2018. STUDY SELECTION: Pre-defined eligibility criteria (written in English, original work-environment instrument for healthcare professionals and not a translation, describing psychometric properties as construct validity and reliability) were used to detect studies describing instruments developed to measure the working environment. DATA EXTRACTION: After screening 6397 titles and abstracts, we included 37 papers. Two reviewers independently assessed the 37 instruments on content and psychometric quality following the COSMIN guideline. RESULTS OF DATA SYNTHESIS: Our paper analysis revealed a diversity of items measured. The items were mapped into 48 elements on aspects of the healthcare professional’s WE. Quality assessment also revealed a wide range of methodological flaws in all studies. CONCLUSIONS: We found a large variety of instruments that measure the professional healthcare environment. Analysis uncovered content diversity and diverse methodological flaws in available instruments. Two succinct, interprofessional instruments scored best on psychometrical quality and are promising for the measurement of the working environment in hospitals. However, further psychometric validation and an evaluation of their content is recommended.